The knowledge and experience with the off-label use - results of a survey - Maria Drenska; Emilia Naseva; Ilko N. Getov (Pensoft Publishers, 2019)
Introduction: The aim of this survey is to assess the current knowledge and experience of medical doctors in regard to off-label use and to determine whether it is legal, according to them, as the local current legislation on medicinal products does neither prohibit nor explicitly permit such use. Materials and methods: One hundred medical doctors from inpatient and outpatient medical care participated and answered 10 questions. The inclusion criteria were to have a degree in medicine and right to prescribe medications. Statistical analysis was performed using the SPSS v19.0 statistical program. Results: The results show that 8 out of 10 medical doctors have knowledge in regard to the meaning of the term "off-label". More than half (62%) stated they have prescribed off-label medicine in their medical practice. Half of the respondents (49%) experienced some kind of trouble when prescribing off-label. In regard to whether the law allows this practice, opinions were divided. To a larger extent (88%), medical doctors support the introduction of clearer rules for off-label use in Bulgaria. Conclusion: Edical doctors have significant knowledge about off-label use, but feel uncertainty in their actions when they use medicines off-label. It is necessary to consider regulating this use at a national level, following the good examples of other European Union (EU) member states, until a harmonized solution within EU is found.